Rome in the North - Hans Kloft (Gephyra, 2019)
Unlike the communities on the Rhine: Xanten, Koblenz, Cologne and Mainz, the medieval cities in central and northern Germany do not have an original Roman past. Whereas during the Humanism and the Renaissance, cities in the north sought in many ways to place themselves in an ancient tradition. The Hanseatic city of Bremen adorned its city hall interiors with Latin sayings and allegories (Justitia, Sapientia, Virtus). The city gates referred to Roman bourgeois virtues. Local historians found a Roman origin in the community long before the reign of the Christian bishop. Ancient culture still characterizes the urban tradition today.